Construction and Validation of the 21 Item Fitness-to-Drive Screening Measure Short-Form - Classen, Sherrilene; Medhizadah, Shabnam; Romero, Sergio; Lee, Mi Jung (Frontiers in Public Health, 2018)
Introduction. The Fitness-to-Drive Screening Measure is a free online screening tool that detects at-risk older drivers, however, it’s 20-minute administration time may render the 54-item tool less than optimal for clinical use. Thus, this study constructed and validated a 21-item FTDS Short-Form (FTDS-SF). Method. This mixed methods study used 200 proxy rater responses and older driver on-road assessments. We conducted a Rasch analysis to examine information at the level of the item and used content validity index scores to select items. Using a receiver operator characteristics curve we determined the concurrent validity of the FTDS-SF to on-road outcomes. Results. Twenty-one items were selected for the FTDS-SF. The area under the curve = .72, indicated the FTDS-SF predicted on-road outcomes with acceptable accuracy. Still, 68 drivers were misclassified. Conclusion. The FTDS-SF may reduce administration time, while still yielding acceptable psychometric properties. Yet, caution needs to be executed in clinical decision making as the measure is overly specific.